Publication Of Unanonimized Decisions On Cases Which Trials Have Been Closed - Tantri Caesar Casanofa Bahtiar; Musakkir Musakkir; Anshori Ilyas (Widya Yuridika, 2023)
This study aims to analyze the implications of publishing decisions that are not anonymized in cases where the trial is carried out in private which results in harm to others, both material and immaterial losses. parties involved in a case. Also, legal remedies that can be taken by parties who feel aggrieved by not anonymizing the decisions that have been published in the decision directory, by which the party can file an objection or report to the relevant court. The results of the study found that the parties who felt aggrieved by not anonymizing the decisions that had been published in the decision directory, or can file an objection or report to the court and the complaint/report will be forwarded to the Supreme Court, and the Supreme Court will follow up through the Supervisory Body at the Supreme Court. court based on unlawful acts of Article 1365 BW. The type of research is empirical legal research, data collection techniques are interviews and literature studies which are then analyzed qualitatively and presented descriptively. or can file an objection or report to the court and the complaint/report will be forwarded to the Supreme Court, and the Supreme Court will follow up through the Supervisory Body at the Supreme Court. court based on unlawful acts of Article 1365 BW. The type of research is empirical legal research, data collection techniques are interviews and literature studies which are then analyzed qualitatively and presented descriptively. parties who feel aggrieved by not anonymizing the decision can file a claim for compensation to the court based on an act that violates the law of Article 1365 BW. The type of research is empirical legal research, data collection techniques are interviews and literature studies which are then analyzed qualitatively and presented descriptively. parties who feel aggrieved by not anonymizing the decision can file a claim for compensation to the court based on an act that violates the law of Article 1365 BW. The type of research is empirical legal research, data collection techniques are interviews and literature studies which are then analyzed qualitatively and presented descriptively.